O Mercado interbancário de câmbio no Brasil - Márcio G. P. Garcia; Fábio Urban (Pontifícia Universidade Católica do Rio de Janeiro (PUC-Rio), Departamento de Economia, 2005)
– We thoroughly describe the workings of the Brazilian interbank exchange rate market: agents, products, regulation, operation and risks. We analyse the recent evolution of the exchange rate market and came to a negative evaluation of the current exchange rate trading system, thereby suggesting an alternative centralized system, more liquid and transparent. We show econometrically that the exchange rate is firstly formed in the exchange rate futures market at the Commodities and Futures Exchange (BM&F), being then transmitted through arbitrage to the spot market.
Keywords: F31; F33; G13; G15; G18; 330; Câmbio; Microestrutura do Mercado de Câmbio no Brasil; Regulaç\~ao; Mercado de câmbio à vista e futuro; Devisenmarkt; Devisenmarkt; Brasilien